Investigating safety aspects of using insect farming to reduce pig and chicken wastes at semi-commercial and lab-scale - L.S. McDowall; A. Collado; R. Clarkson; G. Reiss; K. McDermott (Waste Management, 2026)

Comments on a recently proposed alternative definition for postbiotics - Gabriel Vinderola; Seppo Salminen; Maria Carmen Collado; Akihito Endo; Colin Hill; Sarah Lebeer; Daniel Merenstein; Eamonn M.M. Quigley; Raanan Shamir; Jonathan R. Swann; Hania Szajewska; Daniel J. Tancredi; et al. (Trends in Food Science & Technology, 2025)

Assessing the interconnectivity across complex dimensions of monitoring pelagic species of Sargassum and the role of citizen science - Danielle C. Hatt; Lowell Andrew R. Iporac; Julianna T. Arita; Natalie K. Bally; Ligia Collado-Vides (Harmful Algae, 2025)

Selenium removal from oil refinery wastewater using nanoscale zero-valent iron particles (nZVI) with and without electrochemical peroxidation - M. E. Hansen; S. Collado; C. Gutiérrez; R. Ortiz; P. Lazo; A. Lazo; H. K. Hansen (International Journal of Environmental Science and Technology, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Whistle structure variation between two sympatric dolphin species in the Gulf of California - Simone Antichi; Manali Rege‑Colt; Maia Austin; Laura J. May‑Collado; Óscar Carlón-Beltrán; Jorge Urbán R.; Sergio Martínez-Aguilar; Lorena Viloria-Gómora (Hydrobiologia, 2025)

Long sediment-laden algal turf likely impairs coral recovery on Florida’s coral reefs - A. Duran; K. E. Speare; C. Fuchs; T. C. Adam; L. Palma; M. W. Miller; L. Collado-Vides; A. R. Harborne; D. E. Burkepile (Coral Reefs, 2024)

Characterizing potential resource use of sargasso-dominant sea wrack by terrestrial invertebrate fauna during sargasso influxes in South Florida - Lowell Andrew R. Iporac; W. Ryan James; Ligia Collado-Vides (Estuarine, Coastal and Shelf Science, 2023)

Improving satellite monitoring of coastal inundations of pelagic Sargassum algae with wind and citizen science data - Nathan F. Putman; R. Taylor Beyea; Lowell Andrew R. Iporac; Joaquin Triñanes; Emilie G. Ackerman; Maria J. Olascoaga; Christian M. Appendini; Jaime Arriaga; Ligia Collado-Vides; Rick Lumpkin; Chuanmin Hu; Gustavo Goni (Aquatic Botany, 2023)

Evaluation of physicochemical properties of honey powder using rice and pea proteins as carriers - Taíse Toniazzo; Mar Collado-González; Carmen Cecília Tadini; Alan R. Mackie (Food Research International, 2023)

Species movements within biogeographic regions: exploring the distribution of transplanted mollusc species in South America - Gustavo Darrigran; Ignacio Agudo-Padrón; Pedro Baez; Carlos Belz; Franz Cardoso; Gonzalo A. Collado; Modesto Correoso; María Gabriela Cuezzo; Cristina Damborenea; Alejandra A. Fabres; Monica A. Fernandez; Suzete R. Gomes; et al. (Biological Invasions, 2023)

Intra‐day variability of temperature and its near‐surface gradient with elevation over mountainous terrain: Comparing MODIS land surface temperature data with coarse and fine scale near‐surface measurements - Antonio‐Juan Collados‐Lara; Steven R. Fassnacht; David Pulido‐Velazquez; Anna K.D. Pfohl; Enrique Morán‐Tejeda; Niah B.H. Venable; Eulogio Pardo‐Igúzquiza; Kira Puntenney‐Desmond (International Journal of Climatology, 2021)
Where land surface air temperature data are not available, satellite land surface temperature are used. However, the coarse spatial resolution of satellite‐derived products may yield errors at the local scale. This work shows the differences between the MODIS Land Surface Temperature and Emissivity (MOD11A1) product and ground measurements at two different scales. We used data from 21 SNOTEL stations across the northern Front Range of Colorado to represent the coarse scale and 17 iButton temperature sensors across the Colorado State University Mountain Campus to represent the fine scale. We found significant differences in the temperature and its changes with elevation for the two spatial scales. At the fine scale, cold air drainage can induce an inversion of the temperature gradient with elevation. A higher correlation was found during the nighttime at the fine scale, while, at the coarse scale, higher correlations were observed during the daytime. On windy nights, temperatures do not cool as much as on calmer nights, and the coarse scale near‐surface temperature gradient with elevation persists, though the fine scale inversions do not develop. The near‐surface temperature gradients with elevation based on the MODIS pixels are similar to the ground‐based data at the coarse scale but not at the fine scale. Thus, one must be cautious in selecting the near‐surface temperature gradients with elevation for mountainous terrain when different scales are considered, and a proper validation of satellite products is necessary prior to their use to avoid the propagation of uncertainties.

Multiple late‐Pleistocene colonisation events of the Antarctic pearlwort Colobanthus quitensis (Caryophyllaceae) reveal the recent arrival of native Antarctic vascular flora - Elisabeth M. Biersma; Cristian Torres‐Díaz; Marco A. Molina‐Montenegro; Kevin. K. Newsham; Marcela A. Vidal; Gonzalo A. Collado; Ian S. Acuña‐Rodríguez; Gabriel I. Ballesteros; Christian C. Figueroa; William P. Goodall‐Copestake; Marcelo A. Leppe; Marely Cuba‐Díaz; et al. (Journal of Biogeography, 2020)
Aim Antarctica's remote and extreme terrestrial environments are inhabited by only two species of native vascular plants. We assessed genetic connectivity amongst Antarctic and South American populations of one of these species, Colobanthus quitensis , to determine its origin and age in Antarctica. Location Maritime Antarctic, sub‐Antarctic islands, South America. Taxon Antarctic pearlwort Colobanthus quitensis (Caryophyllaceae). Methods Four chloroplast markers and one nuclear marker were sequenced from 270 samples from a latitudinal transect spanning 21–68° S. Phylogeographic, population genetic and molecular dating analyses were used to assess the demographic history of C. quitensis and the age of the species in Antarctica. Results Maritime Antarctic populations consisted of two different haplotype clusters, occupying the northern and southern Maritime Antarctic. Molecular dating analyses suggested C. quitensis to be a young ( Main conclusions. The Maritime Antarctic populations likely derived from two independent, late‐Pleistocene dispersal events. Both clusters shared haplotypes with sub‐Antarctic South Georgia, suggesting higher connectivity across the Southern Ocean than previously thought. The overall findings of multiple colonization events by a vascular plant species to Antarctica, and the recent timing of these events, are of significance with respect to future colonizations of the Antarctic Peninsula by vascular plants, particularly with predicted increases in ice‐free land in this area. This study fills a significant gap in our knowledge of the age of the contemporary Antarctic terrestrial biota. Adding to previous inferences on the other Antarctic vascular plant species (the grass Deschampsia antarctica ), we suggest that both angiosperm species are likely to have arrived on a recent (late‐Pleistocene) time‐scale. While most major groups of Antarctic terrestrial biota include examples of much longer‐term Antarctic persistence, the vascular flora stands out as the first identified terrestrial group that appears to be of recent origin.

The current status on secondary metabolites produced by plant pathogenic Colletotrichum species - Javier Moraga; Wesley Gomes; Cristina Pinedo; Jesús M. Cantoral; James R. Hanson; María Carbú; Carlos Garrido; Rosa Durán-Patrón; Isidro G. Collado (Phytochemistry Reviews, 2019)

Epicotyl sections as targets for plant regeneration and transient transformation of common bean using Agrobacterium tumefaciens - R. Collado; I. Bermúdez-Caraballoso; L. R. García; N. Veitía; D. Torres; C. Romero; G. Angenon (In Vitro Cellular & Developmental Biology - Plant, 2016)

Understanding the simultaneous biodegradation of thiocyanate and salicylic acid by Paracoccus thiocyanatus and Pseudomonas putida - R. G. Combarros; S. Collado; A. Laca; M. Díaz (International Journal of Environmental Science and Technology, 2016)

SAV Communities of Western Biscayne Bay, Miami, Florida, USA: Human and Natural Drivers of Seagrass and Macroalgae Abundance and Distribution Along a Continuous Shoreline - D. Lirman; T. Thyberg; R. Santos; S. Schopmeyer; C. Drury; L. Collado-Vides; S. Bellmund; J. Serafy (Estuaries and Coasts, 2014)

Comparative genome analysis of Bacillus spp. and its relationship with bioactive nonribosomal peptide production - A. Hamdache; R. Azarken; A. Lamarti; J. Aleu; I. G. Collado (Phytochemistry Reviews, 2013)

The Putative Role of Botrydial and Related Metabolites in the Infection Mechanism of Botrytis cinerea - A. J. Colmenares; J. Aleu; R. Durán-Patrón; I. G. Collado; R. Hernández-Galán (Journal of Chemical Ecology, 2002)

Production of antibacterial activities by members of the family Pseudonocardiaceae: influence of nutrients - G. Platas; R. Morón; I. González; J. Collado; O. Genilloud; F. Peláez; M.T. Diez (World Journal of Microbiology and Biotechnology, 1998)